2021
DOI: 10.13031/trans.14551
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bank Stabilization Structures on Upstream and Downstream Bank Mobilization at Cedar River, Nebraska

Abstract: HighlightsStabilization structures are only effective at stabilized segments.Erosion increased in two of the six segments in the post-stabilization period.Deposition decreased in all six segments in the post-stabilization period.Jetties are effective at reducing erosion but are also prone to fail.Abstract. The effectiveness of streambank stabilization structures is insufficiently quantified. Although such structures clearly reduce or eliminate streambank erosion at the local scale, little is known about associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…These results are similar to those obtained by Russell et al (2021) on the Cedar River in Nebraska in the United States, where tree revetments (or jetties), similar to those installed on the Lower Smoky Hill River, were monitored over a 12‐year period. The researchers found that if tree revetments remained fully or partially functional, bank erosion decreased following installation, supporting the finding that deciduous tree revetments installed on the Lower Smoky Hill River may have decreased bank erosion in the short term.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…These results are similar to those obtained by Russell et al (2021) on the Cedar River in Nebraska in the United States, where tree revetments (or jetties), similar to those installed on the Lower Smoky Hill River, were monitored over a 12‐year period. The researchers found that if tree revetments remained fully or partially functional, bank erosion decreased following installation, supporting the finding that deciduous tree revetments installed on the Lower Smoky Hill River may have decreased bank erosion in the short term.…”
Section: Resultssupporting
confidence: 89%
“…The researchers found that if tree revetments remained fully or partially functional, bank erosion decreased following installation, supporting the finding that deciduous tree revetments installed on the Lower Smoky Hill River may have decreased bank erosion in the short term. However, in the case of revetment failure, Russell et al (2021) also found that bank erosion was exacerbated, above pre‐installation rates. To further evaluate the results obtained on the Lower Smoky Hill River, flow events experienced, bank stratigraphy differences, meander planform characteristics and structure force balance assessments are discussed and incorporated into this analysis in the following discussion sections.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased terrestrial land area, particularly through more permanent tree cover instead of short-lived crop cover, relative to river water and sediments area served as the indicator of streambank stability. In the case of the Little Blue River, the river was dynamic (Figure 2) and we did not attempt to measure river points or segments (e.g., 1.5 meander wavelengths upstream and downstream of stabilized locations with exclusion of segments of channel migration and oxbow formation; Russell et al, 2021). Consequently, we developed an approach to directly measure land cover change in fixed land parcels, from the perspective of erosion management in streambanks and land adjacent to streambanks, rather than an isolated focus on streambanks alone.…”
Section: Introductionmentioning
confidence: 99%